1988
DOI: 10.1111/j.1529-8817.1988.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Ecology of Aureococcus Anophagefferens Gen. Et Sp. Nov. (Chrysophyceae): The Dominant Picoplankter During a Bloom in Narragansett Bay, Rhode Island, Summer 1985

Abstract: Observations of a marked cessation of feeding in _filter feeding animals maintained injowing Narragansett Bay seawater in June 1985 drew our attention to a bloom of a golden alga 2 pm i n diameter at unprecedented populations of 1 O9 cells. L-I. This picoplankter lacked morphological features useful in discriminating it from other similar sized forms with either phase contrast or epzfEuorescence light microscopy. Natural populations of picoplankton, obtained from the height of the bloom until its decline, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 25 publications
0
110
0
1
Order By: Relevance
“…In contrast, Sieburth et al (1988) suggested that even though virus-infected cells were visible throughout a bloom of the small chrysophyte Aureococcus anophagefferens, the bloom declined only after significant numbers of phagotrophic protists developed. They suggested that the viruses primarily influenced the genetic structure of the algal community (species and/or strain composition) rather than its size.…”
Section: Effects On the Diversity Of Microbial Communitiesmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Sieburth et al (1988) suggested that even though virus-infected cells were visible throughout a bloom of the small chrysophyte Aureococcus anophagefferens, the bloom declined only after significant numbers of phagotrophic protists developed. They suggested that the viruses primarily influenced the genetic structure of the algal community (species and/or strain composition) rather than its size.…”
Section: Effects On the Diversity Of Microbial Communitiesmentioning
confidence: 93%
“…It was not until the late 1980s that direct counts of viral abundances in the range of 10 ~ mL ' were reported by Sieburth et al (1988) using epifluorescence microscopy to count virus-sized particles stained with a DNA-specific fluorochrome (DAPI), and by Proctor et al (1988) using TEM. These were followed shortly by estimates ranging from <107 to >10 ~ mL ' for a variety of marine waters (Bergh et al, 1989;Proctor and Fuhrman, 1990), including the Gulf Stream and open ocean.…”
Section: Natural Marine Virus Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The alga was identified and described by Seiburth et al (1988) as the chrysophyte Aureococcus anophagef-ferens gen. et sp. nov.…”
Section: Introductionmentioning
confidence: 99%
“…This alga, named Ostreococcus tauri reached concentrations of 104 to 105 cells/ml. Others have found microeucaryotes to have an increasingly important role in primary production in coastal [22,81,87] and oceanic environments [66].…”
Section: Phytoplankton and The Importance Of Rubpcasementioning
confidence: 99%